The role of religion in politics : the Roman Catholic Church in the Democratic Republic of Congo during the presidency of Joseph Kabila - Maluleke, Tinyiko S. (University of Pretoria, 2022)
Dissertation (MTh (Dogmatics and Christian Ethics))--University of Pretoria, 2020.